Capitalism and Political Strategy in Post-Marxist Discourse Theory. Reply to Jacobs. Issue 1 (2nd January 2021) - Rey-Araújo, Pedro M.
Abstract : In this paper, I provide a short reply to Jacobs's critical appraisal of my previous article, "Ernesto Laclau's Oblivion of Political Economy, " published in this journal, volume 32, number 2 (2020). There, I had argued that Laclau's post-Marxism suffered from a marked incapacity to theorize the extent to which capitalist dynamics affect ongoing hegemonic struggles. In this regard, Jacobs argues that I implicitly resort to an ontological dualism at odds with post-Marxism's ontological stance, from which an essentialist account of capitalist dynamics ensues. I argue that, while remaining firmly within post-Marxism's core ontological assumptions, further theoretical integration of political economy approaches is a promising path for enhancing post-Marxism's usefulness for strategic reflection, as both of us ultimately aim to do.